2015
DOI: 10.1016/j.clon.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the UK Coordinating Centre for Cancer Research Anal Cancer Trial (ACT1) on Population-based Treatment and Survival for Squamous Cell Cancer of the Anus

Abstract: Introduction: Between 1987 and 1994 three randomised phase III trials demonstrated that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Whilst radical abdomino-perineal excision (APE) has been replaced by CRT as primary treatment for most anal cancers, 56 there are a number of uncommon scenarios where there are relative indications for APE as the primary treatment.…”
Section: The Role Of the Surgeon For Locoregional Anal Canal Cancermentioning
confidence: 99%
“…Whilst radical abdomino-perineal excision (APE) has been replaced by CRT as primary treatment for most anal cancers, 56 there are a number of uncommon scenarios where there are relative indications for APE as the primary treatment.…”
Section: The Role Of the Surgeon For Locoregional Anal Canal Cancermentioning
confidence: 99%
“…This approach was taken because of the anticipated challenge of conducting a primary review of empirical examples of cancer research impact evaluation, and to allow a critique of empirical studies in the context of lessons learnt from the wider literature. A primary review would have been difficult because examples of cancer research impact evaluation, for example, the assessment of research impact on clinical guidelines [ 13 ], or clinical practice [ 14 16 ], are often not categorised in publication databases under the umbrella term of research impact. Reasons for this are the lack of medical subject heading (MeSH) search term relating to research impact assessment and the differing definitions for research impact.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Approximately three-quarters of patients with SCCA receive CRT as initial treatment. 10 Through systematic review, 11 we recently reported on 45 studies of patients with SCCA who received either radiotherapy alone (RT) or CRT and noted that 5-year overall survival increased from a mean estimate of 64% in 1980 to 75% in 2010 ( p = 0.046). It is conceivable that this temporal improvement might be driven by improvements in loco-regional control, but might also be due to unmeasured factors, such as general improvement in healthcare, centralisation, improved imaging and radiotherapy delivery, and more effective management of toxicity.…”
Section: Introductionmentioning
confidence: 99%